Subcellular Localization of Arabidopsis 3-Hydroxy-3-Methylglutaryl-Coenzyme A Reductase - Leivar, Pablo (American Society of Plant Biologists, 2005)
Plants produce diverse isoprenoids, which are synthesized in plastids, mitochondria, endoplasmic reticulum (ER), and the nonorganellar cytoplasm. 3-Hydroxy-3-methylglutaryl-coenzyme A reductase (HMGR) catalyzes the synthesis of mevalonate, a rate-limiting step in the cytoplasmic pathway. Several branches of the pathway lead to the synthesis of structurally and functionally varied, yet essential, isoprenoids. Several HMGR isoforms have been identified in all plants examined. Studies based on gene expression and on fractionation of enzyme activity suggested that subcellular compartmentalization of HMGR is an important intracellular channeling mechanism for the production of the specific classes of isoprenoids. Plant HMGR has been shown previously to insert in vitro into the membrane of microsomal vesicles, but the final in vivo subcellular localization(s) remains controversial. To address the latter in Arabidopsis (Arabidopsis thaliana) cells, we conducted a multipronged microscopy and cell fractionation approach that included imaging of chimeric HMGR green fluorescent protein localizations in transiently transformed cell leaves, immunofluorescence confocal microscopy in wild-type and stably transformed seedlings, immunogold electron microscopy examinations of endogenous HMGR in seedling cotyledons, and sucrose density gradient analyses of HMGR-containing organelles. Taken together, the results reveal that endogenous Arabidopsis HMGR is localized at steady state within ER as expected, but surprisingly also predominantly within spherical, vesicular structures that range from 0.2- to 0.6-μm diameter, located in the cytoplasm and within the central vacuole in differentiated cotyledon cells. The N-terminal region, including the transmembrane domain of HMGR, was found to be necessary and sufficient for directing HMGR to ER and the spherical structures. It is believed, although not directly demonstrated, that these vesicle-like structures are derived from segments of HMGR-ER. Nevertheless, they represent a previously undescribed subcellular compartment likely capable of synthesizing mevalonate, which provides new evidence for multiorganelle compartmentalization of the isoprenoid biosynthetic pathways in plants.